Management of black rot disease of rapeseed (Brassica napus)-Indian mustard (Brassica juncea) caused by Xanthomonas campestris pv. campestris - MAURYA, MANISH KUMAR; SINGH, H K; SINGH, S K; SINGH, DINESH (The Indian Journal of Agricultural Sciences, 2022)
Out of 340 genotypes/varieties screened against black rot disease in rapeseed-Indian mustard under field conditions, 15 genotypes found resistant, viz. RTM 1624, RTM 1626, TM EPAU, DRMRAB-7-116, NPJ-177, LES-55, DRMRIJ 16-1, RH 1514, BASANTI, NDRS 1-2, TMR 14-1, TMR- 14-4, TMR 14-5, TMR 14-3, T 27, can be utilized as a donor for the development of black rot disease resistant varieties in crucifer crops. All genotypes of Eruca sativa were found resistant against black rot disease. Under in vitro conditions, streptocycline @200 ppm had maximum inhibition zone 3.8 cm diameter with 73.48% inhibition over control. In vivo, minimum disease severity 13.29% and 14.29%, lowest AUDPC 185.8% and 201.4% and highest yield 16.45 q/ha and 16.62 q/ha was recorded in the treatment T1, Streptocycline @200 ppm on rapeseed-mustard var. NDR 8501 (Narendra Rai) in 2017–18 and 2018–19 respectively.